Hypothalamic–Pituitary–Thyroid Axis Crosstalk With the Hypothalamic–Pituitary–Gonadal Axis and Metabolic Regulation in the Eurasian Tree Sparrow During Mating and Non-mating Periods - Nabi, Ghulam; Hao, Yinchao; Liu, Xuelu; Sun, Yanfeng; Wang, Yang; Jiang, Chuan; Li, Juyong; Wu, Yuefeng; Li, Dongming (Frontiers in Endocrinology, 2020)
Reproduction is an energetically costly phenomenon. Therefore, to optimize reproductive success, male birds invest enough energetic resources for maintaining well-developed testes. The hypothalamic–pituitary–thyroid (HPT) axis in birds can crosstalk with the hypothalamic–pituitary–gonadal (HPG) axis, thus orchestrating both the reproduction and metabolism. However, until now, how the free-living birds timely optimize both the energy metabolism and reproduction via HPT-axis is not understood. To uncover this physiological mechanism, we investigated the relationships among body mass, testis size, plasma hormones including thyroid-stimulating hormone (TSH), thyroxine (T4), triiodothyronine (T3), metabolites including glucose (Glu), triglyceride (TG), total cholesterol (TC), uric acid (UA), diencephalon mRNA expressions of type 2 (Dio2) and 3 (Dio3) iodothyronine deiodinase enzymes, thyrotropin-releasing hormone (TRH), thyroid-stimulating hormone (TSH), gonadotropin-releasing hormone I (GnRH-I), and gonadotropin-inhibitory hormone (GnIH) in a male Eurasian tree sparrow (ETS, Passer montanus). We found significantly larger testis size; elevated diencephalon Dio2 and TRH mRNA expressions, plasma T3, and UA levels; and significantly lowered Glu, TG, and TC levels during mating relative to the non-mating stages in male ETSs. However, Dio3, TSH, GnRH-I, and GnIH mRNA expression did not vary with the stage. Furthermore, life-history stage dependent variation in plasma T3 had both direct effects on the available energy substrates and indirect effects on body mass and testis size, indicating a complex regulation of metabolic pathways through the HPT- and HPG-axes. The identified differences and relationships in mRNA expression, plasma T3 and metabolites, and testis size in male ETSs contribute to our understanding how free-living birds adjust their molecular, endocrinal, and biochemical features to orchestrate their reproductive physiology and metabolism for the maintenance of well-developed testes.